Quantum adiabatic elimination at arbitrary order for photon number measurement. Issue 2 (2020) - Sarlette, Alain; Rouchon, Pierre; Essig, Antoine; Ficheux, Quentin; Huard, Benjamin
Abstract: Adiabatic elimination is a perturbative model reduction technique based on timescale separation and often used to simplify the description of composite quantum systems. We here analyze a quantum experiment where the perturbative expansion can be carried out to arbitrary order, such that: (i) we can formulate in the end an exact reduced model in quantum form; (ii) as the series provides accuracy for ever larger parameter values, we can discard any condition on the timescale separation, thereby analyzing the intermediate regime where the actual experiment is performing best; (iii) we can clarify the role of some gauge degrees of freedom in this model reduction technique.